A Psychosocial Approach to Understanding Underground Spaces - Lee, Eun H.; Christopoulos, George I.; Kwok, Kian W.; Roberts, Adam C.; Soh, Chee-Kiong (Frontiers in Psychology, 2017)
With a growing need for usable land in urban areas, subterranean development has been gaining attention. While construction of large underground complexes is not a new concept, our understanding of various socio-cultural aspects of staying underground is still at a premature stage. With projected emergence of underground built environments, future populations may spend much more of their working, transit, and recreational time in underground spaces. Therefore it is essential to understand the challenges and advantages that such environments have to improve the future welfare of users of underground spaces. The current paper discusses various psycho-social aspects of underground spaces, the impact they can have on the culture shared among the occupants, and possible solutions to overcome some of these challenges.